ENVIRONMENTAL SCANNING AND ORGANISATIONAL PERFORMANCE IN UNILEVER NIGERIA PLC: Array - ONIKOYI, Idris Adegboyega; ODUMERU, James A.; TAJUDEEN, Wasiu Olamilekan; ODEH, Callistus Destiny (The Journal of Accounting and Management, 2022)
The objective of the study is to evaluate the effect of environmental scanning on organisational performance in Unilever Nigeria plc Ikeja, Lagos. Data were collected from both primary and secondary sources. The study adopted survey research design and data were collected through a structured questionnaire from a sample size of 227 and also from the company’s annual report from the period of 2012 to2016. The demographic data collected were analysed using frequency distribution and percentages. The findings revealed that internal environmental analyses affects consumer satisfaction and hence have a positive correlation as shown by the regression co-efficient (r)= .493, also it revealed that internal environmental analysis has significant impact on product quality and a positive correlation or relationship exist as it is revealed by the regression co-efficient (r)= .612 and the last hypothesis also revealed that relationship exist between external environmental analysis and profitability as shown by the regression co-efficient (r) = 0.914782. Based on this, the study concludes that environmental scanning has impact on non-financial orgnaisational performance and however, it is recommended that organisation should continuously, periodically scan and monitor the trends and changes in consumer satisfaction and incorporate changes in taste and preferences of consumers to reflect product quality as it may constitute opportunity and threats to the organisation